1998
DOI: 10.1021/jf9800211
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Glycoside Content and Composition of Tea Infusions Made from Commercially Available Teas and Tea Products

Abstract: The composition and content of flavonol glycosides (FGs) have been measured in infusions of a range of black tea and black tea products. Tea contains a mixture of glycosides of quercetin, kaempferol, and myricetin and the total level of these glycosides, in infusions prepared in a normal domestic manner, for the leaf teas varied from 36.5 to 88.3 mg/L, although greater variation was observed for the tea products, from 7.0 to 428.1 mg/L. Altogether seven quercetin, five kaempferol, and two myricetin glycosides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 13 publications
4
46
0
1
Order By: Relevance
“…These results suggest that either kaempferol is absorbed more efficiently than quercetin, that quercetin is preferentially excreted through the bile compared with kaempferol, or that quercetin is more efficiently converted to other compounds (in the gut, or postabsorption). In tea, kaempferol and quercetin are conjugated to similar moieties (mainly rutinosides; Price et al, 1998), but in onions, quercetin is found conjugated to glucosides (Price & Rhodes, 1997). Quercetin was excreted at an average of 1.1% of intake after onion consumption compared with 0.5% after tea, suggesting that quercetin from onions is more bioavailable than from tea.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that either kaempferol is absorbed more efficiently than quercetin, that quercetin is preferentially excreted through the bile compared with kaempferol, or that quercetin is more efficiently converted to other compounds (in the gut, or postabsorption). In tea, kaempferol and quercetin are conjugated to similar moieties (mainly rutinosides; Price et al, 1998), but in onions, quercetin is found conjugated to glucosides (Price & Rhodes, 1997). Quercetin was excreted at an average of 1.1% of intake after onion consumption compared with 0.5% after tea, suggesting that quercetin from onions is more bioavailable than from tea.…”
Section: Discussionmentioning
confidence: 99%
“…Tannin content of dried persimmon was analyzed according to the method described by modified Prussian Blue assay (Graham, 1992;Price et al, 1988). One hundred milliliters of sample extract was added to 3 mL of distilled water, centrifuged at 10000× g for 15 min, and supernatant was collected.…”
Section: Tannin Contentmentioning
confidence: 99%
“…Blue assay method (Graham, 1992;Price et al, 1988). A 0.1 ㎖ of sample extract was added to 3 ㎖ of distilled water, centrifuged at 10000 × g for 15 min, and the supernatant was After 15 min, absorbance was measured at 700 ㎚ using a spectrophotometer (HP 8452A diode-array, Hewlett-Packard Co.).…”
Section: Tannin Contentmentioning
confidence: 99%